Calculation of K Uptake by Three Crops Grown Under Controlled Conditions Using a Mechanistic Model (University of Khartoum Journal of Agricultural Sciences, 2023)
The aim of this study was to compare simulated and actual Kuptake by three crops, under different K concentrations in the soilsolution, in order to try to explain the underlying mechanisms of nutrientuptake by these crops. In 2002, wheat (Triticum aestivum L. cv. Star),barley (Hordeum vulgare L. cv. Madras) and sugar beet (Beta vulgaris L.cv. C+ T) were grown on a sandy clay loam, with various Kconcentrations in soil solution, in the growth chamber at the Institute ofAgricultural Chemistry, University of Goettingen, Germany. Data werecollected on K transport in soil and uptake by the three crops and used forsimulation by a mechanistic model which encompasses uptake by roothairs as well. To quantify the significance of single soil and plantparameters for nutrient uptake, a sensitivity analysis was carried out.Under sufficient K in the soil solution, where transport was not limitinguptake, the model predicted the actual K uptake correctly. At deficient Kconcentrations, the model over-predicted the K uptake by both wheat andbarley but under-predicted that of sugar beet. The calculatedconcentration profiles around the roots showed that for cereals wrongvalues of the uptake kinetics caused the over-prediction of K uptake,whereas for sugar beet some processes more than was considered by themodel took place.
Keywords: Mechanistic model; uptake kinetics; sugar beet; wheat; barley